1978
DOI: 10.1161/01.cir.57.3.636
|View full text |Cite
|
Sign up to set email alerts
|

Inexcitable right ventricle and bilateral bundle branch block in Uhl's disease.

Abstract: A 29-year-old female with Uhl's anomaly developed complete atrioventricular (A-V) block. His bundle studies revealed block distal to the His bundle recording site with narrow QRS complexes. Right ventricular capture could not be obtained and despite successful left ventricular epicardial pacing, the patient died. Autopsy revealed absence of myocardium in most areas of the right ventricle and the right side of the ventricular septum with a normal tricuspid valve. Conduction system examination revelaed total des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…ARVD is generally considered to be due to abnormality of devetopment mostly affecting the RV. This interpretation fits quite well with the embryologic development of the myocardium [23]. Thus, involvement of the embryologically adjacent LV seems plausible.…”
Section: Gross Pathology and Histologysupporting
confidence: 85%
See 1 more Smart Citation
“…ARVD is generally considered to be due to abnormality of devetopment mostly affecting the RV. This interpretation fits quite well with the embryologic development of the myocardium [23]. Thus, involvement of the embryologically adjacent LV seems plausible.…”
Section: Gross Pathology and Histologysupporting
confidence: 85%
“…usually manifests as varying degrees of infiltration of fat and fibrous tissue that has the same pathological characteristics as in the RV [5,23,[25][26][27][28]. This could be present in a rather limited area of myocardium or could extend to large zones of the LV musculature [29].…”
Section: Fibrofatty Replacement Of Left Ventricular Myocardium Left mentioning
confidence: 99%
“…The one major difference is that in Uhl's case, the patient did not have heart block. However, on careful review of other reported cases, we found that heart block has been seen in Uhl's anomaly in an exceptionally well-studied case in which the conduction system was examined (56) and, furthermore, that heart block is not all that rare in arrhythmogenic right ventricular dysplasia (57, 58), although conduction system studies have been reported in which no anatomical abnormalities were found (59). How all of this may be linked for both Uhl's anomaly and arrhythmogenic right ventricular dysplasia is discussed below.…”
Section: Massive Apoptotic Destruction Of the Right Ventricle And Itsmentioning
confidence: 99%
“…This is in contrast to Uhl's anomaly, where many cases occur in the very young and usually manifest as stillbirth or congestive heart failure in early childhood. 6 The 12-year-old boy described in this report is the youngest patient presenting with this condition in this area. Rheumatic fever is an important and common cause of tricuspid valve regurgitation in our area, and always needs to be ruled out.…”
Section: Discussionmentioning
confidence: 77%